Penggunaan Artificial Intellegence (AI) dalam Membantu Guru Mengembangkan Media Pembelajaran Kreatif bagi Siswa Kelas III di SDN 05 Lembah Beringin - Paratania Jianingsih (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
The rapid development of digital technology has encouraged teachers to become more creative and innovative in designing learning media, especially at the elementary school level. Artificial Intelligence (AI) is one of the technologies that can support teachers in creating attractive, interactive, and effective learning media. This study aims to examine the use of Artificial Intelligence (AI) in helping teachers develop creative learning media for third grade students at SDN 05 Lembah Beringin. This study used a descriptive qualitative method with a literature review approach. Data were collected through the exploration and analysis of academic documents, including scientific journals, books, and proceedings obtained from Google Scholar and other academic databases. The data were analyzed using thematic content analysis to identify patterns, concepts, and important findings related to the implementation of AI in education. The results showed that AI can assist teachers in creating visual learning materials, educational illustrations, interactive worksheets, learning videos, and creative evaluation tools. The use of AI also increased students’ learning motivation, classroom interaction, and teachers’ efficiency in preparing learning materials. In addition, AI-based learning media improved students’ creativity, understanding, and participation during the learning process. Therefore, AI plays an important role in supporting innovative learning practices in elementary schools. The implementation of AI in education is expected to help teachers create more meaningful, engaging, and contextual learning experiences for students in the future.